Assessment of gold mineralization potential in the Tanzania Craton based on stream sediment geochemistry multivariate analysis and regression modeling - Mahamuda Abu; John Desderius Kalimenze; Benatus Norbert Mvile; Samuel Nunoo (Discover Geoscience)
Abstract The artisanal and small-scale mining (ASSM) sector has contributed to economies and is an integral component of the drivers of the gross domestic product (GDP) of most developing countries. To enhance the production of the ASSM sector, most gold (Au) endowed countries have supported the sector’s activities in diverse ways. However, despite this support, several factors, including poor exploration targeting, still affect the sector's production. This study, therefore, seeks to characterize the gold (Au) mineralization and its spatial distribution in the Singida region of the Tanzania Craton with a focus on identifying potential Au mineralized zones that could be demarcated and targeted for ASSM activities and further exploration exercises within the region. The study leverages stream sediment geochemical results to identify the elemental associations and pathfinder elements using multivariate statistics (Principal component analysis), multilinear regression modeling, and spatial distribution of Au and the pathfinder elements within the study area. The Au deposits in the area are strongly associated with the elements; Ni, Cr, V, Mg, Fe, Cu, and Al. Palladium (Pd), platinum (Pt), arsenic (As), and copper (Cu) are the main pathfinder elements in the area. Lead is not directly related to Au from the study. Mafic, ultramafic rocks, and clays are the most probable sources of Au in the area. Gold concentrations are focused on the southwestern fringes of the area. Southwestern, central south, and southeastern fringes of the area should also be explored considering the distribution of the dominant pathfinder elements. Alluvial and lateritic materials are also worth exploring.